Maternal and Fetal Mechanisms of B Cell Regulation during Pregnancy: Human Chorionic Gonadotropin Stimulates B Cells to Produce IL-10 While Alpha-Fetoprotein Drives Them into Apoptosis - Fettke, Franziska; Schumacher, Anne; Canellada, Andrea; Toledo, Natalia; Bekeredjian-Ding, Isabelle; Bondt, Albert; Wuhrer, Manfred; Costa, Serban-Dan; Zenclussen, Ana Claudia (Frontiers in Immunology, 2016)
Maternal immune tolerance towards the fetus is an essential requisite for pregnancy. While T cell functions are well documented, little is known about the participation of B cells. We have previously suggested that IL-10 producing B cells are involved in pregnancy tolerance in mice and humans. By employing murine and human systems, we report now that fetal trophoblasts positively regulate the generation of IL-10 producing B cells. We next studied the participation of hormones produced by the placenta as well as the fetal protein alpha-fetoprotein (AFP) in B cell modulation. Human Chorionic Gonadotropin (hCG), but not progesterone, estrogen or a combination of both, was able to promote changes in B cell phenotype and boost their IL-10 production, which was abolished after blocking hCG. The hCG-induced B cell phenotype was not associated with augmented galactosylation, sialylation or fucosylation of IgG subclasses in their Fc. In vitro, hCG induced the synthesis of asymmetrically glycosylated antibodies in their Fab region. Interestingly, AFP had dual effects depending on the concentration. At concentrations corresponding to maternal serum levels, it did not modify the phenotype or IL-10 secretion of B cells. At fetal concentrations, however, AFP was able to drive B cells into apoptosis, which may indicate a protective mechanism to avoid maternal B cells to reach the fetus. Our data suggests that the fetus secrete factors that promote a pregnancy-friendly B cell phenotype, unraveling interesting aspects of B cell function and modulation by pregnancy hormones and fetal proteins.